Distribution Route of Cement 40’s kg Package at PT.XYZ using Saving Matrix - Nur Rahmawati; Sinta Dewi; M. Dicky Perdana Putra (UNIPA PRESS, 2021)
Determining the distribution route is one important thing that must be considered by the company to get a cheaper product selling price. PT. XYZ is a cement manufacturing company with consumers spread across several regions. Due to the large number of consumers that must be supplied, the company has problems in determining product distribution routes that can produce a low total cost of distribution. In this method, the saving matrix method is used to obtain distribution routes that can produce the minimum distribution costs. From the results of the study, four sub routes of product distribution were found with distance savings of 1176 Km.